The Development of Implicit Memory From Infancy to Childhood: On Average Performance Levels and Interindividual Differences. Issue 2 (21st February 2017) - Vöhringer, Isabel A.; Kolling, Thorsten; Graf, Frauke; Poloczek, Sonja; Fassbender, Ina; Freitag, Claudia; Lamm, Bettina; Suhrke, Janina; Teiser, Johanna; Teubert, Manuel; Keller, Heidi; Lohaus, Arnold; et al.
Abstract : The present multimethod longitudinal study aimed at investigating development and stability of implicit memory during infancy and early childhood. A total of 134 children were followed longitudinally from 3 months to 3 years of life assessing different age‐appropriate measures of implicit memory. Results from structural equation modeling give further evidence that implicit memory is stable from 9 months of life on, with earlier performance predicting later performance. Second, it was found that implicit memory is present from early on, and no age‐related improvements are found from 3 months on. Results are discussed with respect to the basic brain structures implicit memory builds on, as well as methodological issues.